Α Reliability Study of Renewable Energy Resources and their Integration with Utility Grids - Ghania, S. M.; Mahmoud, K. R. M.; Hashmi, A. M. (Engineering, Technology & Applied Science Research, 2022)
Reliability analysis is considered an impressive approach for investigating the planning and design processes of industrial and commercial electrical power distribution systems. Reliability analysis is mainly concerned with the analysis of devices and systems whose individual components are prone to failure risk. The demand for renewable energy resources that work in parallel or replace traditional energy resources is significantly increasing. The current research presents the reliability analysis of the IEEE 40-bus system integrated with large-scale PV and wind systems. Reliability parameters evaluation of power distribution systems will be performed using the zone branch methodology to divide the power system layout into several sections (protected zones). The compensating capacitors will be addressed to clarify their impacts on the system reliability indices. The 40-bus system, known as the IEEE Standard 493-1997, integrated with large-scale PV and wind is simulated using ETAP software. The simulation results reveal that the integration of renewable energy resources with the utility grids can improve the reliability indices. These simulation results are consistent with similar works found in literature and some standards in the field of reliability analysis. The integration of power distribution systems with renewable energy resources improves the reliability indices of the distribution grids.